Forest biomass waste combustion in a pilot-scale bubbling fluidised bed combustor - Tarelho, Luís António da Cruz (2011)
Combustion experiments of forest biomass waste in a pilot-scale bubbling fluidised bed combustor were performed under the following conditions: i) bed temperature in the range 750e800 C, ii) excess air in the range 10e100%, and iii) air staging (80% primary air and 20% secondary air). Longitudinal pressure, temperature and gas composition profiles along the reactor were obtained. The combustion progress along the reactor, here defined as the biomass carbon conversion to CO2, was calculated based on the measured CO2 concentration at several locations. It was foundthat 75e80%of the biomass carbonwasconverted toCO2 in the region located belowthe freeboard first centimetres, that is, the region that includes the bed and the splash zone. Based on the CO2 and NO concentrations in the exit flue gas, it was found that the overall biomass carbon conversion to CO2 was in the range 97.2e99.3%, indicating high combustion efficiency, whereas the biomass nitrogen conversion to NO was lower than 8%. Concerning the Portuguese regulation about gaseous emissions from industrial biomass combustion, namely, the accomplishment of CO, NO and volatile organic compounds (VOC) (expressed as carbon) emission limits, the set of adequate operating conditions includes bed temperatures in the range 750 Ce800 C, excess air levels in the range 20%e 60%, and air staging with secondary air accounting for 20% of total combustion air.